A new genus for the Megatheriinae (Xenarthra, Tardigrada, Megatheriidae) from the Arroyo Chasicó Formation (Upper Miocene) of Buenos Aires Province, Argentina - Brandoni, Diego (2007)
Three Plesiomegatherium species have been described: Pl. hansmeyeri ROTH, the type of the genus, apparently recovered from the Altiplanicie de Abra Pampa, Jujuy (Argentina), Pl. halmyronomum CABRERA, from the Arroyo Chasicó Formation (Buenos Aires Province, Argentina), and Pl. triangulatum RUSCONI from the "Puelchense" of Villa Ballester, Buenos Aires Province (Argentina). This report considers the generic and specific status of Pl. halmyronomum. Analysis of the morphological features available for study indicates that "Pl." halmyronomum and Pl. hansmeyeri are not congeneric, and that Plesiomegatherium is polyphyletic. As Pl. halmyronomum is not assignable to any other known genus, it is placed in the new genus Anisodontherium.